TECHNOLOGICAL METHODS OF ORGANIC FARMING AS A BASIS FOR REGULATING THE DEVELOPMENT OF HARMFUL ORGANISMS - Pysarenko, V. M.; Kovalenko, N. P.; Pospielova, G. D.; Gorb, O. O.; Pischalenko М. А.; Nechyporenko, N. I.; Sherstiuk, O. L. (Scientific Progress & Innovations, 2020)
Organic farming is the concept of harmonious development in the field of agricultural production which ensures the preservation of soil fertility, its protection from xenobiotic contamination and the production of environmentally friendly food products. One of the main principles of organic farming is strict compliance with the requirements for each stage of agricultural production. That is why it is important to find effective technologies. The influence of technological methods of organic farming on the regulation of pests’ development is studied based on many-year experience at the private enterprise “Agroecology” in Shyshaky district of Poltava region. It has been found that the optimization of phytosanitary conditions of crops in organic farming is based on the formation of heterogeneous species and varietal structure of agro-ecosystems, taking into account the economic thresholds of pests, pathogens and weeds, and the peculiarities of technologies inherent in this system. It has been proven that due to application of sufficient amounts of organic fertilizers, growing perennial legumes and green manure crops at the private enterprise “Agroecology” provides optimal nutrition for crops, which helps to increase their competitiveness with weeds and resistance to damage by some pests and diseases. The microbiological activity of soil in organic farming is 28.4–31.6% higher than in intensive agricultural production. In addition, changes in the species composition of entomofauna have been noted. There has been an increase in the number of carnivorous turuns species in the fields of the farm by 20 % compared to crops of cereals with the use of intensive technologies. During the years of research (2012–2019), the dynamic carnivorous carabids’ density, depending on the species composition and weather conditions in organic farming, exceeded this indicator in fields with intensive technology by 32.6– 51.2 %. It was found that the reduction of weediness of crops was associated with compliance with the regulations of technological measures provided for organic farming such as long-term shallow tillage, use of green manure, harvesting of some crops for green fodder, silage, haylage or hay in the phase of mowing ripeness. Widespread use of the principles of agro-phytocenology based on the expansion of species and varietal composition of cultivated plants, lack of pesticides and adherence to the principles of poly-culture contribute to the increase in efficiency of natural entomophagous and fungistasis biocenosis, which in turn allows to control pests on the farm.